Chronic traumatic encephalopathy: a potential late effect of sport-related concussive and subconcussive head trauma - Gavett, B. E.; Stern, R. A.; McKee, A. C. (Clinics in Sports Medicine, 2011)
Chronic traumatic encephalopathy (CTE) is a form of neurodegeneration believed to result from repeated head injuries. Originally termed dementia pugilistica because of its association with boxing, the neuropathology of CTE was first described by Corsellis in 1973 in a case series of 15 retired boxers. CTE has recently been found to occur after other causes of repeated head trauma, suggesting that any repeated blows to the head, such as those that occur in American football, hockey, soccer, professional wrestling, and physical abuse, can also lead to neurodegenerative changes. These changes often include cerebral atrophy, cavum septi pellucidi with fenestrations, shrinkage of the mammillary bodies, dense tau immunoreactive inclusions (neurofibrillary tangles, glial tangles, and neuropil neurites), and, in some cases, a TDP-43 proteinopathy. In association with these pathologic changes, disordered memory and executive functioning, behavioral and personality disturbances (eg, apathy, depression, irritability, impulsiveness, suicidality), parkinsonism, and, occasionally, motor neuron disease are seen in affected individuals. No formal clinical or pathologic diagnostic criteria for CTE currently exist, but the distinctive neuropathologic profile of the disorder lends promise for future research into its prevention, diagnosis, and treatment.